The Potential Role of Indonesia’s Universal Health Coverage in Management of Severe-To-Profound Hearing Loss through Cochlear Implantation - Trimartani, Trimartani; Wibowo, Adik (UI Scholars Hub, 2018)
This study aimed to evaluate the role of Jaminan Kesehatan Nasional (JKN) in improving the quality of cochlear implant services using Strength, Weakness, Opportunity, and Threat (SWOT) analysis. The study identified the internal factors of the cochlear implant center in Cipto Mangunkusumo Hospital as a consideration for developing hospital policies and the external factors to determine strategies for future development. The role of JKN was highlighted on the SWOT analysis, showing that the cochlear implant center was strategically located, thus increased the quality and the competitive factor compared to other hospitals. Strength-Opportunity strategy was recommended in improving service quality and identifying the possibility of JKN and other grants to cover the cost and improve the services, research, and education. The SWOT of the Cochlear Implant Center was identified as: 1. Good internal condition (average score of the strengths is superior to the weaknesses), 2. Good external condition (average score of the opportunities is higher than the threats), 3. Using strengths to maximize the opportunities and alternative strategy to be an aggressive strategy. 4. The role of JKN presented in the SWOT quadrants would give JKN a potency and important role in improving the treatment of severe hearing impairment in Indonesia.